PERBEDAAN NILAI INDEKS GLIKEMIK DAN BEBAN GLIKEMIK NASI PECEL BERAS CIHERANG, BERAS MERAH DAN BERAS SINTANUR - Parmi, Parmi; Isnawati, Muflihah; Setiadi, Yuwono (Poltekkes Kemenkes Semarang, 2016)
Background: The glycemic index is a value that indicates the ability of a carbohydrate-containing foods in improving blood sugar. Previous research also done extensive research on the glycemic index of a food, but every meal we consume some foods and through various treatment processes This study will calculate the glycemic index prepared foods namely pecel distinguished from varieties of rice such as rice Ciherang that have a low glycemic index (55), brown rice has a medium glycemic index (59) and Sintanur rice has a high glycemic index (91). Based on this background, researchers interested in researching on the difference in value of glycemic index and glycemic load of rice pcel of three kinds of rice. Objective: To determine differences in the value of glycemic index and glycemic load on Ciherangpecel of rice, red rice, and rice Sintanur. Methods: This study used an experimental research design. There were three treatment groups each group consisting of 9 people. After 10 hours of fasting blood glucose measurements were taken and given 50 grams of carbohydrates such as white bread 95 grams. Blood glucose levels were measured again at minute 15, 30, 45, 60, 90 and 120. An interval of one week, the subjects were given pecelciherang rice, red rice and rice Sintanur, subsequently re-measured blood glucose as the first treatment. Results: The value of rice IG pecelCiherang rice was 86.67, 86.69 pecel brown rice and rice pecelSintanur 90.59. Pecel glycemic load of 43.82 Ciherang rice, red rice 43.95 and 45.38 Sintanurpecel rice.